Beetle and cactus-inspired surface endows continuous and directional droplet jumping for efficient water harvesting. Issue 3 (9th December 2020) - Wang, Xikui; Zeng, Jia; Li, Jing; Yu, Xinquan; Wang, Zuankai; Zhang, Youfa
Abstract : A bionic hybrid wetting surface inspired by the desert beetle and cactus for efficient water harvesting. Abstract : Efficient water harvesting from vapor has attracted increasing attention in recent years owing to its potential to address the daunting water crisis. However, a fundamental challenge limiting the water collection efficiency from vapor is the intrinsic trade-off between fast droplet nucleation and efficient droplet removal, both of which have distinctively opposite requirements in surface chemistry and morphology. Inspired by the elegant topography features and functions of desert beetles and cactus thorns, herein, we designed a novel hybrid wetting surface consisting of wedge-shaped patterns, in which the patterns mimic the bumpy back of the desert beetle for enhanced water nucleation, whereas the wedge-shaped topography renders unconventional oblique droplet jumping and long-range transport. The synergistic cooperation of these two effects effectively decouples the inherent trade-off, leading to more than an 11 times increase in water harvesting compared to that of a superhydrophobic surface. Thus, our findings have extensive applications in water harvesting, power generation and desalination.